(untitled) (Revista científica Olimpia, 2020)
Current times require the enhancing of values related with independent activity and the development of a systematic practice of physical exercises. Several investigations relate the physical activity with the stimulation of memory procceses as a main aspect in the formation of education professionals. In the Pre-school Major there are some insuficiencies in the practice of physical exercises which hinder the stimulation of the students´ memories. Therefore, the present work is aimed at proposing physical exercises to enhance Pre-school students´ memories. Basically, the use of dancing therapies is suggested, due to the fact that they actívate the students´ physical condition and better up the heart, mental, and muscular activities. Besides, the work includes the benefits of this activity from the psychological point of view and the actions to follow up.